2022
DOI: 10.1111/jcpp.13563
|View full text |Cite
|
Sign up to set email alerts
|

Altered theta–beta ratio in infancy associates with family history of ADHD and later ADHD‐relevant temperamental traits

Abstract: Background Uncovering the neural mechanisms that underlie symptoms of attention deficit hyperactivity disorder (ADHD) requires studying brain development prior to the emergence of behavioural difficulties. One new approach to this is prospective studies of infants with an elevated likelihood of developing ADHD. Methods We used a prospective design to examine an oscillatory electroencephalography profile that has been widely studied in both children and adults with ADHD – the balance between lower and higher fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…One example of a well-studied phenomenon is the relationship between the theta/beta ratio and ADHD (Ogrim, Kropotov, & Hestad, 2012; Liechti et al, 2013). Recent studies showed that a higher theta/beta ratio was related to a higher risk of ADHD in 10mo infants (Begum-Ali and colleagues, 2022). However, the study by Donoghue and colleagues (2020a) found that aperiodic components conflate the theta/beta ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of a well-studied phenomenon is the relationship between the theta/beta ratio and ADHD (Ogrim, Kropotov, & Hestad, 2012; Liechti et al, 2013). Recent studies showed that a higher theta/beta ratio was related to a higher risk of ADHD in 10mo infants (Begum-Ali and colleagues, 2022). However, the study by Donoghue and colleagues (2020a) found that aperiodic components conflate the theta/beta ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although research on higher frequency bands in infants is still scarce, a study by Tierney and colleagues (2012) suggests a reduction of frontal beta and gamma between the fifth month and the second year of life. In addition, the relative power in different frequency bands is relatet to individual differences in cognitive development (Anderson & Perone, 2018; Bell & Wolfe, 2007; Benasich et al, 2008; MacNeill et al, 2018; Whedon et al, 2020) and in infants at risk of neurodevelopmental disorder (Arns et al, 2013; Begum-Ali et al, 2022; Gabard-Durnam et al, 2019; Tierney et al, 2012), which signal its relevance.…”
mentioning
confidence: 99%
“…Some studies have focused on pregnant mothers with ADHD, following their offspring over time (Gustafsson et al, 2020;Sullivan et al, 2015). As described earlier, these designs have produced novel and intriguing findings in recent years (Begum-Ali et al, 2022;Joseph et al, 2022;Miller et al, 2021;Sullivan et al, 2015), suggesting that they are both feasible and fruitful.…”
Section: Methods Measurement and Study Designmentioning
confidence: 99%
“…See Table 1 for summary statistics of the included sample and Fig. 2 for a breakdown of participant retention at each time point [adapted from [45]].…”
Section: Samplementioning
confidence: 99%